High Carbohydrate Antigen 19-9 Levels Indicate Poor Prognosis of Upper Tract Urothelial Carcinoma - Jeong, Seung-hwan; Han, Jang Hee; Jeong, Chang Wook; Kim, Hyeon Hoe; Kwak, Cheol; Yuk, Hyeong Dong; Ku, Ja Hyeon (Frontiers in Oncology, 2022)
Upper tract urothelial carcinoma (UTUC) occurs in urothelial cells from the kidney and the ureters. Carbohydrate antigen 19-9 (CA 19-9) is a tumor marker for pancreatic and gastrointestinal cancers, and its high levels are associated with poor prognosis in bladder cancer. In this study, prospective patients enrolled in the registry of Seoul National University were retrospectively examined to determine the clinical significance of CA 19-9 in UTUC. In 227 patients, high serum CA 19-9 levels reflected a high tumor burden represented by high T and N stages, leading to adverse prognosis in metastasis-free or overall survival. Subsequently, propensity score matching analysis showed that the CA 19-9 level is an independent prognostic factor of UTUC.